Waste management at Waste Bank Mutiara (The Gade Clean & Gold) Tuah Madani District: Pengelolaan Sampah pada Bank Sampah Mutiara (The Gade Clean & Gold) Kecamatan Tuah Madani - Juwita Oktavia; Benny Yulianto; Denai Wahyuni; Syukaisih Syukaisih; Novita Lusiana (Badnur Medisa Group, 2022)
Mutiara Waste Bank (The Gade Clean & Gold) is a Unit Waste Bank in Pekanbaru which does not have waste management data in National Waste Management Information System since 2019. Several problems related to waste management in this Waste Bank were found, namely : re-sorting Waste Bank managers from waste that has been sorted by customers, piles of garbage that fill garbage storage area and irregular waste transportation. The purpose of this research was to find out in-depth information about waste management at Waste Bank Mutiara. Data were collected using interview guidelines and observation sheets, then analyzed using triangulation techniques. The research subjects were 5 people, 1 key informant, 1 main informant and 3 supporting informants. The results showed that waste management at Mutiara Waste Bank was not optimal. There were facilities and infrastructure have not been fulfilled, such as uninsulated waste storage areas and unavailability of containers equipped wish label/signs. The transportation at Mutiara Waste Bank is carried out if several types of waste have reached one car or at least half a car, causing the accumulation waste in the waste storage area. Recommended to the manager of the Mutiara Waste Bank to complete the facilities and infrastructure, as well as to socialize and implement a reward system to increase public interest in waste collection which can affect the increase of frequency of transportation.